2014
DOI: 10.3892/ijo.2014.2730
|View full text |Cite
|
Sign up to set email alerts
|

Oxime bond-linked daunorubicin-GnRH-III bioconjugates exert antitumor activity in castration-resistant prostate cancer cells via the type I GnRH receptor

Abstract: It is well established that gonadotropin-releasing hormone receptors (GnRH-R) are expressed in different types of cancers, including castration-resistant prostate cancer (CRPC) and mediate the antiproliferative effect of GnRH analogs. Thus, these compounds are employed as targeting moieties to selectively deliver chemotherapeutic agents to cancer cells. GnRH-III, the decapeptide isolated from the sea lamprey brain, has lower potency than GnRH in stimulating gonadotropin secretion, but it exerts antiproliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…A similar enhanced antitumor activity was also detected for conjugates modified with acylated 4 Lys in the HT-29 human colon [ 19 ], LNCaP [ 17 ] and DU145 [ 37 ] human prostate cancer cell lines compared to the conjugate containing native GnRH-III sequence. Despite the increased activity of conjugates substituted with acylated 4 Lys, they displayed their dose-dependent cytotoxic activity at higher concentrations comparing to the free Dau.…”
Section: Resultssupporting
confidence: 54%
“…A similar enhanced antitumor activity was also detected for conjugates modified with acylated 4 Lys in the HT-29 human colon [ 19 ], LNCaP [ 17 ] and DU145 [ 37 ] human prostate cancer cell lines compared to the conjugate containing native GnRH-III sequence. Despite the increased activity of conjugates substituted with acylated 4 Lys, they displayed their dose-dependent cytotoxic activity at higher concentrations comparing to the free Dau.…”
Section: Resultssupporting
confidence: 54%
“…In humans, as reported for GnRH-II, also GnRH-III seems to exert its effects through the activation of the classical form of GnRHRs (Montagnani Marelli et al, 2015); however, GnRH-III seems to exert a significant anti-tumour effect on human cancer cells expressing the GnRHR, while causing very low activity on gonadotrophin secretion in mammals (Kovacs et al, 2002).…”
Section: Gnrhrsmentioning
confidence: 84%
“…In our laboratory, we investigated the antitumor activity of bioconjugates consisting of daunorubicin linked to the GnRH-III isoform in CRPC cells. We found that these compounds are rapidly internalized and exert a significant antitumor activity in these cells [ 292 ]. Further studies are needed to confirm the efficacy and the lack of toxicity of GnRH-based cytotoxic bioconjugates in PCa.…”
Section: Androgen and Gonadotropin-releasing Hormone Receptors: Molecular Targets For Therapeutic Strategies In Crpcmentioning
confidence: 99%